THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF WINDARO PERMAI VILLAS MEDIATED BY CONSUMER PURCHASING DECISIONS - Ditya Jessica; Berampu, Lailan Tawila; Wasnury , Rendra (Universitas HKBP Nommensen, 2025)
The increasingly competitive property business requires developers to deliver high-quality products and services to improve customer satisfaction and purchasing decisions. Villa Windaro Permai, as a housing developer, needs to understand the factors influencing customer satisfaction, both directly and through purchasing decisions. This study aims to analyze the influence of product quality and service quality on customer satisfaction at Villa Windaro Permai, as well as to examine the mediating role of purchasing decisions in this relationship. This research uses a quantitative approach with a survey method. The data analysis technique applied is path analysis using SPSS software. The sample consists of 100 respondents who are customers of Villa Windaro Permai housing complex. The findings indicate that product quality and service quality have a positive and significant influence on customer satisfaction, both directly and indirectly through purchasing decisions as a mediating variable. Moreover, customer satisfaction has a dominant influence on purchasing decisions, positioning it as a strategic factor in encouraging property purchases.